Back Cover: Parallel Ghost Imaging (Adv. Quantum Technol. 10/2020). Issue 10 (5th October 2020) - Qiu, Xiaodong; Zhang, Dongkai; Ma, Tianlong; Lin, Fei; Guo, Haoxu; Zhang, Wuhong; Chen, Lixiang
Abstract : Based on two‐photon hyperentanglement – that is, two photons simultaneously entangled in polarization, color (wavelength), and spatial modes – Lixiang Chen and co‐workers develop a new parallel ghost imaging system of different independent imaging channels (see article number 2000073 ). These channels are encoded and sustained by polarization and wavelength multiplexing while in each channel spatial entanglement is always maintained to convey the ghost images in parallel.